The Benefits of e-Business Performance Measurement Systems - Hinton, Matthew (Elsevier, 2011)
To participate fully in the new world of e-business, organisations have to make significant financial investments. How then, should they evaluate e-business investment proposals and monitor the resulting performance of their on-line business operations? To what extent are traditional performance measurement systems fit for a world where clicks not bricks determine business success? This CIMA report describes research investigating how organisations have been adapting their performance measurement systems for e-business. The research aimed to identify the features and benefits of an effective e-business performance measurement system by studying twelve organisations that have had some success in developing performance measurement systems suitable for the on-line environment.